Investigating the Meaning of Nurun Ala Nurin “A Study of Falsafi Tafsir on Divine Light in Qur'an” - Didi Darmadi; Sudjiat Zubaidi; Muhammad Zhilal (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The phrase “Nurun ala Nurin